Indole-3-propionic acid mitigates chlorpyrifos-mediated neurotoxicity by modulating cholinergic and redox-regulatory systems, inflammatory stress, apoptotic responses and DNA damage in rats (2022)
This study probed the neuroprotective influence of indole-3-propionic acid (IPA) in rats exposed to chlorpyrifos (CPF) alone at 5 mg/kg body weight or co-administered with IPA at 12.5 and 25 mg/kg for 14 days. Behavioral data indicated that IPA significantly (p < 0.05) abated CPF-mediated anxiogenic-like behaviors with concomitant improvement in the locomotor and exploratory behaviors as substantiated by track plots and heat maps data. Also, IPA mitigated CPF-mediated diminution in cholinergic and antioxidant defense systems whereas it mark- edly improved thioredoxin level and thioredoxin reductase activity in cerebral and cerebellar tissues of the animals. Co-administration of IPA significantly enhanced anti-inflammatory cytokine, interleukin-10 but sup- pressed oxidative and inflammatory stress, caspase-9 and caspase-3 activation with concomitant reduction in 8- hydroxy-2'-deoxyguanosine (8-OHdG) level and histological damage. Collectively, IPA-mediated neuro- protection involves modulation of cholinergic and redox-regulatory systems, inflammatory stress, apoptotic re- sponses and DNA damage in cerebrum and cerebellum of rats.